1994
DOI: 10.1016/0735-1097(94)90126-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic characteristics of lesion formation and time course of smooth muscle cell proliferation in a porcine proliferative restenosis model

Abstract: Early thrombus formation is minimal, and thrombus accounts for a small portion of subsequent neointimal formation. Smooth muscle cell proliferation and matrix formation are the major factors relating to neointimal formation in this proliferative model of restenosis. The evolution of neointimal formation after coronary stenting shows maximal smooth muscle cell proliferation at 7 days, with a decline to low levels by 28 days. Therefore, these data may be useful for developing effective therapies for restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(97 citation statements)
references
References 24 publications
5
88
1
3
Order By: Relevance
“…The degree of arterial injury induced at the time of angioplasty is a major predictor of the neointimal response. 41,42 Our experimental model of coronary angioplasty causes deep arterial injury and medial tears with exposure of the external elastic lamina. As shown in the Table, the degree of injury did not differ between coronary arteries taken from the two groups.…”
Section: -11mentioning
confidence: 99%
“…The degree of arterial injury induced at the time of angioplasty is a major predictor of the neointimal response. 41,42 Our experimental model of coronary angioplasty causes deep arterial injury and medial tears with exposure of the external elastic lamina. As shown in the Table, the degree of injury did not differ between coronary arteries taken from the two groups.…”
Section: -11mentioning
confidence: 99%
“…3,4 Thrombus deposition and acute inflammation are followed by a granulation tissue response with neovascularization, SMC migration and proliferation, and the replacement of acute by chronic inflammatory cells. 5 ECM molecules are synthesized by neointimal SMCs. Experimental arterial injury studies demonstrate that the neointima remodels over time with changes in proteoglycans and replacement of type III collagen with type I collagen.…”
mentioning
confidence: 99%
“…Many animal experiments showed that denudation or overstretch injuries led to neointimal hyperplasia (4,9,(35)(36)(37)(38). At the cellular level, SMC proliferation is an important factor for neointimal hyperplasia.…”
Section: Neointimal Hyperplasia Stimulated By Mechanical Injurymentioning
confidence: 99%
“…However, restenosis is a problem often encountered and is mainly due to neointimal hyperplasia and vascular remodeling (2)(3)(4)(5)(6)(7)(8)(9)(10). Stent insertion decreases the restenosis rate, probably by physically blocking negative vascular remodeling, but it cannot prevent neointimal hyperplasia that resulted from smooth muscle cell (SMC) proliferation (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%